Of Men, Machines and Apocalypses: Masculine Anxieties in Indian Speculative Fiction - Dibyadyuti Roy (Boibhashik, 2015)
Exploding bombs embedded with catastrophic potential have remained central to our eschatological conceptualizations for more than a century. Future war fiction—a key sub-genre of speculative fiction—in building upon this obsession introduces us to unforeseen apocalyptic settings, which are brought forth through a nexus between gendered bodies and destructive military machinery. In underscoring the decidedly masculine nature of future war fiction, this article explores depictions of anxious postcolonial masculinity within the little-explored terrain of Indian speculative fiction. Apocalyptic settings in these texts, I argue, provide a topos for enacting postcolonial masculine anxieties, which are subsequently countered through making male bodies contingent on the volatile performances of destructive military technology. In utilizing R.W Connell’s conceptualization of “hegemonic masculinity,” I explore the reasons behind the emergence of postcolonial masculine insecurities, which, I argue, results from India’s colonial history and its continued legacy within the subcontinent. Finally, my examination of representative Indian speculative texts, namely Mainak Dhar’s Line of Control (2009) and Sami Ahmad Khan’s Red Jihad (2012) emphasizes that making hegemonic postcolonial masculinity contingent on the destructive capabilities of military technology results in unstable and threatening masculine performances; much like the unpredictable nature of war machinery highlighted in these texts.